Hubungan Kemampuan Membaca Dengan Keterampilan Menulis Cerita Pendek Pada Siswa Kelas VI SDS Bhakti Luhur - Nisya Fahira; Sholehuddin Sholehuddin (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This study is based on the background of 6th grade students of SDS Bhakti Luhur, there are internal and external barriers for novice writers. These obstacles include a lack of knowledge, not having a good command of language, and a lack of interest in writing, while external factors that prevent someone from writing are the difficulty of finding topics or ideas for writing material. The purpose of this study was to determine whether there is a relationship between reading ability and short story writing skills in grade VI students of SDS Bhakti Luhur. This study uses a quantitative approach by using the survey method. The population of this study amounted to 24 students. The entire population was used as a research sample. Data collection techniques in this study were carried out by filling out a questionnaire. The data analysis technique uses the correlation test and the coefficient of determination (R2) test. The results of this study indicate that there is a relationship between reading ability and short story writing skills, this is evidenced by the results of the correlation test which produces a correlation value (rxy) of 0.635> r table compared to the r table value of N = 26 and df = N-2 = 24 obtained 0.635.Then the percentage of the relationship between reading ability and short story writing skills is 37.6%.This is evidenced by the results of the coefficient of determination (R2 ) test conducted by researchers.This research can be useful for teachers in order to improve reading skills and writing skills in students.